Harmonized detail specification for fixed metallized polyethylene terephthalate film dielectric d.c. capacitors (long-life grade). Rectangular insulated non-metallic case, rigid radial terminations. Full assessment level. (15th February 1981) - British Standards Institution,
No abstract available